G-Protein coupled receptors: structure and function in drug discovery. Issue 60 (1st October 2020) - Odoemelam, Chiemela S.; Percival, Benita; Wallis, Helen; Chang, Ming-Wei; Ahmad, Zeeshan; Scholey, Dawn; Burton, Emily; Williams, Ian H.; Kamerlin, Caroline Lynn; Wilson, Philippe B.
Abstract : The G-protein coupled receptors (GPCRs) superfamily comprise similar proteins arranged into families or classes thus making it one of the largest in the mammalian genome. Abstract : The G-protein coupled receptors (GPCRs) superfamily comprise similar proteins arranged into families or classes thus making it one of the largest in the mammalian genome. GPCRs take part in many vital physiological functions making them targets for numerous novel drugs. GPCRs share some distinctive features, such as the seven transmembrane domains, they also differ in the number of conserved residues in their transmembrane domain. Here we provide an introductory and accessible review detailing the computational advances in GPCR pharmacology and drug discovery. An overview is provided on family A-C GPCRs; their structural differences, GPCR signalling, allosteric binding and cooperativity. The dielectric constant (relative permittivity) of proteins is also discussed in the context of site-specific environmental effects.